2022
DOI: 10.3390/horticulturae8070586
|View full text |Cite
|
Sign up to set email alerts
|

Terroir Traceability in Grapes, Musts and Gewürztraminer Wines from the South Tyrol Wine Region

Abstract: This study arose from the need to relate specific terroir aspects with experienced sensory properties of Gewürztraminer wines from Tramin (northern Italy). A multidisciplinary approach was used to investigate seven vineyards’ ecological characteristics, including geology and geographical features. A geopedological method using Vineyard Geological Identity (VGI) and Solar Radiation Identity (SRI) for topoclimatic classification, as well as multi-parameter measuring stations of air and soils, elicited analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Overall, the field microclimate observation data more accurately reflected the characteristics of the vineyard microclimate than the national reference station data. This result is consistent with a previous study that listed the temperature variation characteristics between a microclimate station and a weather station and concluded that microclimate station data could better represent vineyard climate [11,[20][21][22][23][24][25].…”
Section: Climate Quality For Wine Grape In 2019 and 2020supporting
confidence: 92%
“…Overall, the field microclimate observation data more accurately reflected the characteristics of the vineyard microclimate than the national reference station data. This result is consistent with a previous study that listed the temperature variation characteristics between a microclimate station and a weather station and concluded that microclimate station data could better represent vineyard climate [11,[20][21][22][23][24][25].…”
Section: Climate Quality For Wine Grape In 2019 and 2020supporting
confidence: 92%
“…This map visually represents the relationships between keywords in the existing research on terroir. The trend of increasing terroir research articles could be attributed to a combination of factors, including growing interest in wine and agriculture, [19,20] advances in research methods, [21,22] global expansion of wine production, consumer demand for authenticity and quality, [23][24][25][26]and the interdisciplinary nature of terroir as a research subject. [27][28][29] The frequency of the term "terroir" in different countries can provide insights into the prominence and popularity of this concept in various regions.…”
Section: Methodsmentioning
confidence: 99%